LAW COMPLIANCE WITH THE IMPLEMENTATION OF HINDU RELIGIOUS CEREMINIES IN THE CITY OF MATARAM IN THE FRAMEWORK OF MAINTENANCE OF SOCIAL SOLIDARITY DURING THE COVID-19 PANDEMIC - I Gusti Komang Kembarawan (Prodi Hukum Agama Hindu Jurusan Dharma Sastra IAHN Gde Pudja Mataram, 2022)
This study was conducted to analyze legal compliance in the implementation of Hindu religious ceremonies in the city of Mataram in the context of maintaining social solidarity during the COVID-19 pandemic. This phenomenon is related to the adaptation of the implementation of Hinduism in Mataram city regarding Social Restrictions during the Corona Virus Pandemic (Covid-19). This research is designed in a qualitative descriptive type. The results of this study obtained three answers from the formulation of research problems. First, legal compliance in carrying out religious ceremonies for Hindu communities in the city of Mataram in the midst of the implementation of social restrictions in preventing the spread of the COVID-19 pandemic is still being carried out by conditioning and complying with health protocols. Second, legal compliance in the implementation of Hinduism is indicated by a change in the implementation of religious ceremonies which are no longer performed lively, but are regulated by avoiding crowds. Third, legal compliance in a small scope is applied in carrying out religious ceremonies in the family environment and as much as possible reducing the implementation of religious ceremonies outside the home. Although there are people who carry out religious ceremonies outside their homes, they are required to comply with health protocols.